Effekte körperlicher Aktivität und körperlichen Trainings auf den psychischen Status bei älteren Menschen mit und ohne kognitive Schädigung - Wiloth, Stefanie; Lemke, Nele; Hauer, Klaus (Zeitschrift für Gerontologie und Geriatrie, 2012)
Fear of falling and depression in the elderly and among cognitively impaired people lead to restrictions in quality of life. Being more active is associated with improved mental health as documented in cross-sectional and longitudinal studies. This is especially true for depression. Such epidemiologic evidence is lacking in fear of falling. This review summarizes current evidence from epidemiological and randomized controlled trials (RCTs) and gives an outlook for future research perspectives. The majority of studies included in this review document a significant reduction of depression and fear of falling in older persons by physical training with less evidence in persons with cognitive impairment. With respect to intensity, duration, and amount of exercise, evidence-based recommendations were limited by the small number of high-quality comparative RCTs. High-intensity strength or endurance training was the most effective for reducing depression, while participation in Tai-Chi or multifactorial training programs was most effective to reduce fear of falling.
Gesehen am 06.12.2018